Pemberdayaan Fungsi Organisasi dalam Mewujudkan SDM Nelayan yang Unggul pada Koperasi Ikhtiar Swadaya Mitra (ISM) Karya Sinar Bahari, Desa Tanggul Jaya, Kelurahan Banten, Kecamatan Kasemen, Kota Serang, Provinsi Banten - Prayogi, Munawir; Santoso, Mohamad; Waluyani, Dyah Oktabriawatie; Dalianti, Indana; Septiani, Kurnia Rahmah; Sugiarti, Endang; Catio, Mukhlis (Jurnal PKM Manajemen Bisnis, 2024)
Community Service entitled Empowerment of Organisational Functions in Realising Superior Fisherman Human Resources at ISM Karya Sinar Bahari Cooperative, Tanggul Jaya Village, Banten Village, Kasemen District, Serang City, Banten Province. This community service activity is to provide education to the community, especially members of the ISM Karya Sinar Bahari Cooperative regarding the importance of organisational functions to realise superior Fisherman Human Resources at the ISM Karya Sinar Bahari Cooperative, Serang City, Banten. The method used is a survey method and direct delivery of material as well as simulations and discussions regarding the application of Human Resources (HR) management science in realising superior Fisherman HR at the ISM Karya Sinar Bahari Cooperative, Serang City, Banten.